Answer:
k=3
Explanation:
Given equation is
![x^2+y^2 -6y-12=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/kntpy0rzgr89o7zcc8139sad5khpmr864z.png)
First we move -12 to the other side by adding 12 on both sides
![x^2+y^2 -6y =12](https://img.qammunity.org/2019/formulas/mathematics/high-school/m1xtjwxo2o36i52nifqw20zjqommgtob0v.png)
We apply completing the square method to get square form (y-k)^2
Lets take coefficient of y and then divide it by 2
-6 divide by 2 is -3
Then we square it (-3)^2 = 9
We add 9 on both sides
![x^2+y^2 -6y + 9=12+9](https://img.qammunity.org/2019/formulas/mathematics/high-school/wxdba918d82l3ov3c8vlx0m1bvd5vtf0r9.png)
![x^2+(y^2 -6y + 9)=21](https://img.qammunity.org/2019/formulas/mathematics/high-school/9n9i0rb08zo6xs1tdh4809cqtt6epc3vs5.png)
Now we factor, y^2 - 6y +9 is (y-3)(y-3)= (y-3)^2
![x^2+(y-3)^3=21](https://img.qammunity.org/2019/formulas/mathematics/high-school/xt9zr0lz7kekdemv73xjfeqy2rgd1h4w4q.png)
Now we compare with x^2 + (y-k)^2 = 21 and find the value of k
The value of k = 3